(untitled) (Journal of Informatics Education and Research, 2026)
This study examines the challenges associated with the implementation of the free education policy and its implications for secondary school management effectiveness in Zambia. Using a qualitative research design based on secondary data, the study analyses trends in enrolment, resource allocation, teacher availability, and administrative practices. The findings indicate that while the policy has significantly increased access to secondary education, it has also introduced considerable pressures on school management systems. Key challenges identified include overcrowded classrooms, inadequate infrastructure, financial constraints, teacher shortages, and inconsistencies in policy implementation. These factors collectively affect the ability of school administrators to maintain organisational efficiency and ensure quality teaching and learning outcomes. The study highlights the complex relationship between increased access and management capacity, emphasising the need for aligning policy implementation with resource availability and institutional preparedness (UNESCO, 2017; World Bank, 2018).